Design And Development Multi-Service Access Node (Msan) Lock - Sukiman, Nurul Zakiyyah (Universiti Sains Malaysia, 2017)
The increasing of stealing Multi-Service Access Node (MSAN) or equipment in the TM roadside cabinet cases caused a huge losses faced by Telekom Malaysia ™. The valuable of MSAN which value thousands of Malaysia Ringgit get the attention of the irresponsible user for stealing and selling the equipment to gain their own profit. The stealing cases do not even caused to losses but effected the phone and internet networking. The interruption takes hours to endure the problem. In solving the problem, a study of design and development of MSAN lock is investigated through the concept of design and development process. An interview with a TM’s personnel was conducted to obtain information on the problem faced by the customers. The next process is collecting data of appropriate design concept and convey all the design concept to Solidworks software (3D drawing). Next, the process followed by election of three of the design concept that are closest to the desired product concept. The final concept will be selected through a process of testing the concept and determination of the final specification. Lastly, the final concept is fabricated as a prototype model and cost analysis process is done. Selection of the final concept is discussed and chosen via a feedback from the TM worker itself. In addition, material selection for the final concept design is discussed to generate a durable and strong lock that can protect the MSAN from stealing. Other than that, the justification for the selected design are debated by showing the proof of concept.